2004
DOI: 10.1002/ejlt.200300876
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oil conditioning on the permeate flux and cake properties during microfiltration of lampante olive oil

Abstract: This work studies the deacidification of lampante virgin olive oil (acidity ranging from 2.15-4.65%) by microfiltration through alumina membrane. The effects of (i) the amount of absorbed water during the neutralization of the free fatty acids with various NaOH concentrations, and (ii) the acid pre-treatment with phosphoric acid on permeate fluxes during microfiltration were studied. Physical properties of the cake (specific resistance and compressibility) were also investigated. The soap molecules are known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Table VI presents characteristics of the permeate regarding turbidity, OGC, TOC, and TSS after treatment of the oily wastewater for 4.5 h. It can be observed that TOC in the permeates of M1, M2, M3, and M4 hollow fiber membranes is 1.8, 0.4, 0.2, and 0.2 mg/L, respectively. As expected, the rejection of M3 (PES/PAN; 75/25 wt%) membrane is 35 , and Jegatheesan et al 36 for more details), and thus the process can meet the environmental standards related to discharged materials.…”
Section: Performance Of the Synthesized Pes And Pes/pan-blended Hollosupporting
confidence: 58%
See 1 more Smart Citation
“…Table VI presents characteristics of the permeate regarding turbidity, OGC, TOC, and TSS after treatment of the oily wastewater for 4.5 h. It can be observed that TOC in the permeates of M1, M2, M3, and M4 hollow fiber membranes is 1.8, 0.4, 0.2, and 0.2 mg/L, respectively. As expected, the rejection of M3 (PES/PAN; 75/25 wt%) membrane is 35 , and Jegatheesan et al 36 for more details), and thus the process can meet the environmental standards related to discharged materials.…”
Section: Performance Of the Synthesized Pes And Pes/pan-blended Hollosupporting
confidence: 58%
“…For the all measurements, the M3 (PES/PAN; 75/25 wt%) membrane exhibited better performance than M1 and M2 hollow fiber membranes. The PES/PAN (75/25 wt%) blend hollow fiber membranes were found practically suitable for the treatment of industrial oily wastewater with rejection of OGC at the level of 0.2 mg/L (99.7%), resulting in the permeate with OGC below 5 mg/L (see Salahi et al, Hafidi et al, and Jegatheesan et al for more details), and thus the process can meet the environmental standards related to discharged materials.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of this kind of wastewater requires reliable purification systems to meet environmental discharge standards (oil content < 5 ppm) . Membrane-based separation processes, particularly microfiltration (MF) and UF processes, are proving to be promising alternatives for conventional industrial separation methods, due to their numerous advantages such as high selectivity, easy separation, mild operation, continuous and automatic operation, no need for extraneous chemicals, high-purity products, much lower environmental impact, and economical and fast operation, as well as relatively low capital and running investment. According to previous studies, high volumes of domestic, industrial, oil-in-water, and oily wastewaters were treated with MF and UF processes to exceptionally high-quality standards, usually for reuse purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane based separation processes are becoming a promising technology. This technology has several advantages including high selectivity, easy separation, mild operation, small area requirement, continuous and automatic operation, economic and fast operation, and low running investment. Previous studies showed that microfiltration (MF) processes are compatible with environmental standards. However, membrane fouling that typically forms by inorganic and organic materials existence in the oily wastewaters is the major problem in using membranes for oily wastewater treatment. , …”
Section: Introductionmentioning
confidence: 99%